UPAYA MENINGKATKAN HASIL BELAJAR IPA MELALUI PENERAPAN MODEL MIND MAPPING - Heti Purnamadewi (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2020)
This research was motivated by the low science learning outcomes in class VII MTs Negeri 2 Pangandaran. The research objective was to improve the science learning outcomes of class VII-V students of MTs Negeri 2 Pangandaran through a mind mapping learning model. The method used is classroom action research. The research was conducted in 2 cycles, each cycle consisting of two meetings. The research subjects were students of class VII-C MTs Negeri 2 Pangandaran, totaling 30 students, consisting of 14 male students and 16 female students. The results showed that the average student learning outcomes increased from 54.55 before the pre-action to 63.33 in the first cycle of meeting 1 and increased to 70 in the first cycle of meeting 2. In cycle 2 the average learning outcomes increased from 78 in findings. 1 to 84 at the meeting 2. Based on the completeness data it can be concluded that the application of the mind mapping model can improve the learning outcomes of class VII-C students in the science subject at MTs Negeri 2 Pangandaran.